Game development tool essentials - Arnaud, Remi; Berinstein, Paula; Franco, Simon; Herubel, Adrien; McCutchan, John; Nedelcu, Nicusor; Nitschke, Benjamin; Robinet, Fabrice; Ronchi, Christian; Samour, Gustavo; Turkowski, Rita; Walter, Robert; et al. (Apress, 2014)
Game Development Tool Essentials provides must-have tips and tricks from industry professionals for strengthening and streamlining your game tools pipeline. Everyone knows the game tools pipeline is important, but in the current environment of shrinking budgets and increased time pressure, developers often have to settle for inefficient, ad hoc, messy pipelines.  This unique book will break you out of that cycle. The practical, expert insights contained within will enable you to work faster and more efficiently, so you can spend more time making cool things. Game Development Tool Essentials pools the knowledge and experience of working developers over four critical aspects of the game tools pipeline: asset and data management, geometry and models, Web tools, and programming. Within those sections, you will learn cutting-edge techniques on essential subjects such as COLLADA rendering, exporting and workflow; asset management and compiler architecture; and moving tools to the cloud. If you're a game developer, you need Game Development Tool Essentials. Covers readily available tools and tools developers can build themselves. Presents 96 code samples, 81 illustrations, and end-of-chapter references. Special chapter on moving tools to the cloud.